2020
DOI: 10.1111/jce.14699
|View full text |Cite
|
Sign up to set email alerts
|

Unintended ICD discharge in a patient undergoing bladder tumor resection utilizing monopolar cautery and full‐body return electrode

Abstract: Patients with cardiac implantable electronic devices (CIED) and implantable cardioverter-defibrillator (ICD) devices frequently present for surgical procedures. If electrocautery is used, careful planning is needed to avoid inappropriate device function or device damage. Published consensus statements suggest that if the surgery is below the umbilicus, interference is typically minimal, and therefore it is not recommended to reprogram or disable the CIED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Our case and the other cited cases indicate that the ASA Practice Advisory should consider additional factors other than the location of the surgery when monopolar electrocautery is utilized [3][4][5]. Our case is unique in that it illustrates that the recommendations of Singleton et al [3], including distance to the sensing electrode, patient height, and underbody dispersion electrode, may not be enough.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Our case and the other cited cases indicate that the ASA Practice Advisory should consider additional factors other than the location of the surgery when monopolar electrocautery is utilized [3][4][5]. Our case is unique in that it illustrates that the recommendations of Singleton et al [3], including distance to the sensing electrode, patient height, and underbody dispersion electrode, may not be enough.…”
Section: Discussionmentioning
confidence: 70%
“…Other cases of underbody dispersion pads associated with inappropriate ICD therapy have been reported [ 4 , 5 ]. As proposed by Singleton et al [ 3 ], the current may have traveled close enough to the sensing electrode despite a far distance to the pacemaker generator.…”
Section: Discussionmentioning
confidence: 99%
“…The level of EMI was considered to be high in the cardiac subjects, however the authors were unable to determine if use of the pad contributed to the EMI since they had no comparative control of a conventional adhesive electrode. Lefevre et al [14] observed ICD discharges when using electrosurgery during bladder surgery with the Mega Soft pad under the patient's torso. Tully et al [15] also observed ICD discharges when using electrosurgery during sacral debridement with the Mega Soft pad under the patient's torso.…”
Section: Use In Patients With Implantable Devicesmentioning
confidence: 99%